EKSPLORASI ETNOMATEMATIKA PADA AKTIVITAS JUAL BELI DI PASAR KERAMAT - Khapsari, Dewi Indah; Anjariyah, Deka; Feriyanto (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This study aims to describe the mathematical concepts applied in buying and selling transactions at Pasar Keramat. To utilize contextual mathematics learning, students must learn mathematical concepts from everyday life because abstract mathematics causes difficulties for those who learn it. Buying and selling activities at Pasar Keramat have characteristics that raise the concept of buying and selling during the Majapahit Kingdom, namely using gobog coins. This study uses a qualitative method with an ethnographic approach. Data collection was carried out through observation, interviews, and documentation. Data analysis used methods developed by Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of the study found that the mathematical concepts applied in buying and selling activities at Pasar Keramat use the concept of circle geometry in transaction tools, the concept of basic algebra with the use of the variable gb (gobog), the concept of comparison of value in comparing the value of gobog coins with rupiah, and the concept of social arithmetic.